West Bank and Gaza : Public Expenditure and Financial Accountability Assessment, 2018 - World Bank (World Bank, Washington, DC, 2020)
This Public Expenditure and Financial Accountability (PEFA) assessment is intended to enhance the effectiveness of West Bank and Gaza’s (WB&G) PFM systems and to aid the Palestinian Authority to consolidate its ongoing and planned reforms. More specifically, the assessment has undertaken an independent review of the quality and performance of PFM systems in WB&G for the financial years 2015, 2016 and 2017, and of the medium-term budget for 2018-21. In doing so, it provides a diagnostic analysis that can be used as the basis for dialogue on PFM reforms that will inform future updates and design work on the PFM reform strategy and subsequent action plans. Additionally, this work will inform the Monitoring and Evaluation Framework and will enhance the dialogue between the WB&G and its Development Partners and other key stakeholders.